The Moderating Effect of Company Size on The Relationship Between Financial Performance and Corporate Zakat Expenditure During Covid-19 - Mursid, Mansur Chadi; Asis, Daryl M. De; Aenurofik, Aenurofik (Universitas Islam Negeri Raden Intan Lampung, 2024)
The purpose of this study is to analyze the impact of profitability on Zakat expenditures using firm size as a moderating variable in Indonesian Islamic commercial banks. Data was obtained from the official websites of Islamic commercial banks surveyed from 2014 to 2020. Moderated regression analysis with SPSS program was used as the data analysis method. The findings show that ROA has a positive impact on firms' Zakat expenditures, while GPM and BOPO have no effect on firms' Zakat expenditures. Firm size moderates the relationship between profitability and firms' Zakat expenditures.